Author Correction: Functional 5′ UTR mRNA structures in eukaryotic translation regulation and how to find them. Issue 10 (October 2018) - Leppek, Kathrin; Das, Rhiju; Barna, Maria
The legend of Figure 1 has been modified to remove misleading referencing to evolution. The title of the legend has been modified from 'Evolutionary expansion of eukaryotic 5' UTR lengths' to 'Interspecies variation in 5' UTR lengths'; the first sentence of the legend has been modified from 'The length of 5' untranslated regions (UTRs) has increased in eukaryotes during evolution…' to 'The length of 5' untranslated regions (UTRs) varies in eukaryotes…'. The changes have been made in the HTML and PDF versions of the manuscript.